2022
DOI: 10.1038/s41437-022-00533-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and post-transcriptional regulation of checkpoint genes on the tumour side of the immunological synapse

Abstract: Cancer is a disease of the genome, therefore, its development has a clear Mendelian component, demonstrated by well-studied genes such as BRCA1 and BRCA2 in breast cancer risk. However, it is known that a single genetic variant is not enough for cancer to develop leading to the theory of multistage carcinogenesis. In many cases, it is a sequence of events, acquired somatic mutations, or simply polygenic components with strong epigenetic effects, such as in the case of brain tumours. The expression of many gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 176 publications
0
6
0
Order By: Relevance
“…In addition, although Duan et al demonstrated that mir-195-5p is inversely linked with immune cell infiltration in lung adenocarcinoma [ 65 ], the precise molecular mechanism has not been investigated. Dobosz et al showed that miRNAs can also be involved in tumor-cell–immune-cell interactions by regulating post-transcriptional regulation of immune checkpoint genes [ 66 ], which made mir-195-5p development as a small molecule drug more challenging. Taken together, these results demonstrated the tumor therapeutic effect of FASN inhibition by mir-195-5p and future studies may take a new direction into the involvement of mir-195-5p and FASN in the tumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although Duan et al demonstrated that mir-195-5p is inversely linked with immune cell infiltration in lung adenocarcinoma [ 65 ], the precise molecular mechanism has not been investigated. Dobosz et al showed that miRNAs can also be involved in tumor-cell–immune-cell interactions by regulating post-transcriptional regulation of immune checkpoint genes [ 66 ], which made mir-195-5p development as a small molecule drug more challenging. Taken together, these results demonstrated the tumor therapeutic effect of FASN inhibition by mir-195-5p and future studies may take a new direction into the involvement of mir-195-5p and FASN in the tumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…These ICMs are small proteins expressed at the cell surface membrane that need to be either activated or inactivated to trigger immune responses. 48 ICMs suppress the ability of the CD8+ T-cells of the immune system to recognize the malignancy as a target for eradication. These ICM proteins include PD-L1 and PD-L2, both of which are recognized by the PD-1 receptor on T-cells.…”
Section: Alterations In Icmsmentioning
confidence: 99%
“…Tumour cells express ICMs to regulate and suppress host response, and facilitate tumour cell survival. These ICMs are small proteins expressed at the cell surface membrane that need to be either activated or inactivated to trigger immune responses 48 . ICMs suppress the ability of the CD8+ T‐cells of the immune system to recognize the malignancy as a target for eradication.…”
Section: Immune Escape As Alternative Mechanism Of Post‐hct Relapsementioning
confidence: 99%
See 1 more Smart Citation
“…microenvironment [2][3] . Immune checkpoint gene expression often reduces autoimmune reactivity, and its presence in tumor cells stops the immune system from clearing malignancies 4 . Furthermore, immunological checkpoint genes (ICGs) represent novel targets for cancer therapeutic development 5 .The basement membrane (BM) is the oldest extracellular matrix (ECM) in animals and is made up of several components.…”
Section: Introductionmentioning
confidence: 99%